Olympic Education as a chance of reducing the phenomenon of youngsters dropping out from educational system - Czechowski, Marcin (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The work includes analysis of the basis of the Olympic Education Concept and its use in prevention of school dropout. Olympic Education is supported by the values of modern Olympic and sport. Its theoretical grounds constitute sport pedagogy developed by Baron Pierre de Coubertin. Coubertin did not create any particular educational system and didn’t introduce any definition of sport pedagogy. The lack of the rigid concept can be considered as a quality. It enables us to use the olympism and its rules to solve many problems of continuously developing World, which emerge from the needs of new generations and challenges they face. New methodological conceptions based on Olympic values have been created for decades. It is expected that the conceptions can bring many benefits for individuals and social groups. New programs have been developed, their implementation area has been broadened in order to form proper social attitudes as well as amending various pathological phenomenon. There is a strong premise to introduce the Olympic values to school system in order to boost the efficiency of educational work mainly to achieve better pupils motivation for learning and to strengthen integration of the school environment.